The relation of visfatin with nausea and vomiting in the pregnancy - Farnaz Jahani (Journal of Research in Medical Sciences, 2020)
Background: The etiology of nausea and vomiting during pregnancy (NVP) is unclear and appears multifactorial. It has been shown that the physiological changes associated with NVP include changes in the levels of adipocytokines. Therefore, we investigated the association of nausea and vomiting during pregnancy with visfatin, β-human chorionic gonadotropin (βHCG), and perceived stress. Materials and Methods: In this cross-sectional study, 100 nulliparous pregnant women aged 18–45 years were evaluated. Participants completed two questionnaires including the Index of Nausea, Vomiting, and Retching (INVR) and Perceived Stress Scale (PSS) in the three trimesters of pregnancy. They also referred to the laboratory to conduct the biochemical examinations including serum visfatin and βHCG levels in three trimesters. The obtained data were analyzed by SPSS 16 using statistical repeated-measures analysis of variance, Friedman, Bonferroni, and Wilcoxon post hoc tests. Marginal model (method generalized estimating equation [GEE]) was performed to assess the predictors of the INVR in the participants. Results: INVR, PSS, visfatin, and βHCG levels significantly decreased from the first trimester to the third trimester of pregnancy (P ≤ 0.001). As a result of simple marginal model (GEE method), visfatin was predicted log βHCG (P = 0.035). Furthermore, the multiple marginal model revealed that the two predictors of βHCG (P = 0.01) and PSS (P ≤ 0.001) were positively correlated with the INVR. Furthermore, visfatin had an indirect positive effect on INVR. Conclusion: The present study showed that visfatin can be indirectly related with nausea and vomiting throughout pregnancy. Furthermore, it seems that fluctuations in visfatin levels are independent of weight gain during pregnancy.